A Simple, Readily Accessible, and Effective Apparatus for the Photoisomerization of cis-Cyclooctenes to trans-Cyclooctenes - Pickel, Thomas C.; Genung, Nathan E.; Guckian, Kevin M.; Shi, Xianglin (Synlett, 2021)
A simple, cost effective, and readily accessible apparatus for the photoisomerization of cis-cyclooctenes to trans-cyclooctenes is described. Utilizing only FEP tubing, aluminum vent pipe, a household germicidal lamp, and a flash chromatography system, trans-cyclooctenes can be prepared in good yield.
Keywords: trans-cyclooctene; photochemistry; bioconjugation; click chemistry; flow chemistry